A systematic literature review on waqf governance - Nursyahida Zulkifli,; Mohd Nasir Ismail,; Ghazali Osman,; Zulkarnain Yusoff, (Penerbit Universiti Kebangsaan Malaysia, 2022)
As the concept of waqf is continuously explored worldwide, it becomes a mainstream discipline embedded in most organizations. Waqf governance is important for the development of waqf properties for the sustainability and wealth of the Muslim communities. Most of the literature identified that the management of waqf is under the jurisdiction of the state government. It shows that the management and governance of the Waqf should be improved and become the main concern of the current researchers since the development of waqf has provided significant contributions to the socio-economic of the nation. This paper is aimed to provide a systematic literature review of waqf governance. The studies on the waqf governance were initiated in 2011 and it showed growing trends related to the publications on waqf governance starting 2017. A total of 49 documents published between 2011-2021 were retrieved. 19 related documents are included for further analyses based on the systematic searching strategies process. In this contribution, we propose a systematic literature review by partitioning the literature into papers addressing waqf governance. The waqf governance is vital to ensure that the administrators able to cope with the competitive management so that the properties are managed and developed successfully especially in the post pandemic.